Determinants of interconnected corporate information. Evidence of the connectivity principle in integrated reporting - Pilar Tirado-Valencia; Marta de Vicente-Lama; Magdalena Cordobés-Madueño; Mercedes Ruiz-Lozano (European Research on Management and Business Economics)
This paper aims to deepen knowledge of the principle of connectivity between financial and non-financial information defined in the Integrated Reporting (IR) conceptual framework. We have created a multidimensional connectivity index that is used to assess the level of connectivity in reporting. The results indicate that the levels achieved are low, suggesting that firms publishing their reports under the IR conceptual framework have not fully internalised this principle. Our results also show that coercive and normative institutional factors such as the mandatory nature of IR or the legal system, drive connectivity. Connectivity is also generally influenced by internal managerial decisions mainly related to the report's length and assurance. These findings may have practical implications for regulators and standard-setters, who should explicitly incorporate this principle into their pronouncements, providing guidelines to facilitate its practical implementation, and for preparers who should enhance the interactivity of reports.